2016
DOI: 10.3389/fenvs.2016.00069
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High and Low Levels of Plant-Beneficial Heavy Metal Ions on Plant Growth and Development

Abstract: Heavy metals (HMs) exists in the environment in both forms as essential and non-essential. These HM ions enter in soil biota from various sources like natural and anthropogenic. Essential HMs such as cobalt (Co), copper (Cu), iron (Fe), manganese (Mn), molybdenum (Mo), nickel (Ni), and zinc (Zn) plays a beneficial role in plant growth and development. At optimum level these beneficial elements improves the plant's nutritional level and also several mechanisms essential for the normal growth and better yield of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
85
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(121 citation statements)
references
References 107 publications
4
85
0
3
Order By: Relevance
“…and Mg, while Al and Cu in the liquid products were found to decrease when compared with those in raw manure (Table 1). Although the concentrations of Fe and Zn increased to some extent after HTT, only 0.78 and 1.33 mg/L were detected in L150-60, respectively, which are much lower than the reported limit values that inhibit plant growth and the national effluent standards in Japan (Arif et al, 2016;Ko et al, 2008; MOE, 2015).…”
Section: Fertilizer Potential Of Liquid Product From Hydrothermally Tmentioning
confidence: 59%
“…and Mg, while Al and Cu in the liquid products were found to decrease when compared with those in raw manure (Table 1). Although the concentrations of Fe and Zn increased to some extent after HTT, only 0.78 and 1.33 mg/L were detected in L150-60, respectively, which are much lower than the reported limit values that inhibit plant growth and the national effluent standards in Japan (Arif et al, 2016;Ko et al, 2008; MOE, 2015).…”
Section: Fertilizer Potential Of Liquid Product From Hydrothermally Tmentioning
confidence: 59%
“…In the long-term Zn experiment, no changes were observed in L 0 , Gs or E in plants treated with the low Zn concentration, but growth was correlated to an enhanced photosynthetic rate (A) at the optimal Zn (25 µM) dose. It has been previously reported that photosynthesis, carbonic anhydrase activity and chlorophyll concentrations were correlated with Zn nutrition at low levels [51,52]. However, at high Zn concentration a reduced stomatal conductance was in consonance with L 0 reductions and a photosynthetic rate decrease in pak choi.…”
Section: Growth Root Hydraulic Conductance and Gas Exchange Parametersmentioning
confidence: 78%
“…Transport of metal(loid) ions from roots to leaves is performed via membrane transporters, amino acids and/or organic acids (Jabeen et al, 2009). The maintenance of metal-ion homeostasis and plant tolerance in plants is enabled by some families of transporters in roots and leaves: a) influx transporters: ZIP/IRT family of proteins (zinc-iron regulated protein permease) and NRAMP protein (natural resistance-associated macrophage protein); b) efflux transporters: HM-ATPase, CDF (cation diffusion facilitator), CAX (cation exchanger) and ABC (ATPbinding cassette transporters) (Yang et al, 2005;Arif et al, 2016;Castro et al, 2018) (Figures 3B,C). Plant tolerance to deficiency or toxicity of metal(loid)s can be achieved by excluding the element from further course of transport or its accumulation in plant cells (Baker, 1987).…”
Section: Uptake Transport Tolerance and Cross-talk Between Metal(lomentioning
confidence: 99%